PSYCHOLOGICAL DISTRESS EXPERIENCES OF INDIAN POPULATION DURING CORONAVIRUS DISEASE PANDEMIC SOCIAL ISOLATION AND LONELINESS: A CROSS-SECTIONAL STUDY - GOEL, DIVYA; FAROOQ, MAJID (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The sudden emergence of wide spread of the coronavirus disease 2019 (COVID-19) pandemic has led to adoption of physical distancing or lockdown all over the globe to curtail the viral transmission. Although lockdown plays an important role, at the same time, it can adversely affect the psychological health of the population. In addition, because of stay at home order, people are more inclined to use the media which can further aggravate the mental health issues in population. This study was planned to study the perceived psychological issues associated with the COVID-19 pandemic lockdown. Methods: An online social survey was conducted using semi-structured questionnaire, participants were added through snowball sampling technique. Results: A total of 455 people (264 females and 191 males) participated in the study. Majority of participants 228 (50.1%) felt stressed out during coronavirus lockdown period. Female gender was associated with greater negative psychological impact of lockdown. Most participants 263 (57.8%) were worried about the health of the loved ones. Most of the participants tried to seek information from different media. The difference between the stress level was highly significant (p=0.04639∗) between the participants depending on the duration for which they explore the information on different media. Conclusion: COVID-19 pandemic was associated with stress in the majority of people in our sample, and media has a role to modulate the psychological impact of this lockdown. As COVID-19 pandemic is still ongoing, we need to verify these findings on larger population and policy-makers need to strengthen our mental health programs to mitigate the psychological impact of this pandemic.